Analysis Criteria and Indicator Estimation Smart City in South Tangerang City, Banten Province (An Analysis through Smart Economy) - Lubis, Iman; Nasution, Ahmad Yani; Safii, Mohamad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
This research describes indicator smart economy in South Tangerang City. This research purpose to give information for Mayor South Tangerang City how competitive her economic city is. The method is used by fishbone. The indicators for smart economy are innovation spirit, entrepreneurship, image and trademarks, productivity, international embedded and flexibility of labour market. The results are that Indicators smart economy South Tangerang city describes that the residences in South Tangerang city are low innovation, high entrepreneur, growth productivity, low flexibility, local product which only krupuk jengkol is favourite food, and economic image and trademarks which have not large market, and companies that have issued stock are available. In South Tangerang City, it does not put productivity (Manpower Agency) and international embedded (Tourism Agency) as smart economy, but manpower agency is smart social and tourism agency is smart brand.